Art & Magic : Curating the Western Art Witch Movement - Turley-Sonne, Kathryn, (Arts, Creativities, and Learning Environments in Global Perspectives ;, 2024)
The magical images and protest tools of Artemisia Gentileschi to Amanda Yates Garcia, also known as the Oracle of LA, are revealed in this book. Art Witches have created powerful images that resonate with beauty and activism, from Italian courtrooms in the 1500s to binding spells for the US Trump presidency in 2016. For the first time, this book connects the genealogy of the image of the witch from historical to contemporary artists. It intertwines artistic purpose with social ills and equity issues and probes how this narrative is exposed and curated in museums and memorials focused on witchcraft. The collection of images, artist interviews, and a case study of the two artists that make up Hilma's Ghost provide recognition and a new context for this important and rapidly growing art movement.